US phytosanitary restrictions: the forgotten non-tariff barrier. Issue 1 (21st March 2016) - Jouanjean, Marie-Agnes; Maur, Jean-Christophe; Shepherd, Ben
Abstract : Purpose: This paper aims to provide new evidence that the US phytosanitary regime is associated with a restrictive market access environment for fruit and vegetable products. One chief reason seems to be that the US regime uses a positive list approach, under which only authorized countries can export. Design/methodology/approach: The methodology of the paper is primarily qualitative. This paper reviews the US sanitary and phytosanitary measures (SPS) system and its scope for use to protect markets, in addition to protecting life and health. The approach is institutional and political economic. Findings: For most products, only a portion of global production is authorized for export to the USA. Even among authorized countries, only a small proportion is actually exported. As a result, the number of countries exporting fresh fruit and vegetables to the USA is far lower than those exporting to countries like the EU and Canada, but it is on a par with markets known to be restrictive in this area, such as Australia and Japan. Using a data set of fruit and vegetable market access and political contributions, this paper also provides evidence showing that domestic political economy considerations may influence the decision to grant market access to foreign producers. Originality/value: The US SPS system has not previously been analyzed in this way, and the distinction between negative and positive list approaches is highlighted in terms of its implications for third-party exporters. Similarly, the analysis of political contributions is novel and suggestive of an important dynamic at work in the determination of the US policy.